Representation of an Exotic Girl in Conrad’s An Outcast of the Islands: A Postcolonial Study - Hariyono Hariyono; Achmad Choiron; Imron Amrullah; Cicilia Tantri Suryawati (Universitas Lambung Mangkurat, 2026)
This study examines the representation of an exotic girl in Joseph Conrad’s An Outcast of the Islands. It analyzes how a Western author portrays Aissa, a girl from the Dutch East Indies, whose dark brown skin and physical appearance are constructed through the author’s discourse of exoticism. The analysis focuses specifically on Aissa as the object of exoticism, rather than on the fertility of the land of Borneo or the culture of the natives. The term “exotic,” historically constructed through colonial discourse, is therefore examined through the portrayal of Aissa as a native girl from the Dutch East Indies. The study explores how Conrad’s representation aligns with colonial stereotypes, emphasizing power relations between the colonizer and the colonized. The research applies Tyson’s postcolonial reading strategies and Huggan’s concept of postcolonial exoticism. The method used is descriptive qualitative analysis with textual examination. The findings reveal that Aissa functions as a literary construct that reinforces colonial imagination: exoticism as a commodity, marginal discourse, a literary representation strategy, and the construction of authenticity. This research contributes to understanding how cultural bias and gendered colonial perspectives remain embedded in modern Indonesian cultural perception. The implication highlights the need to deconstruct internalized colonial stereotypes still influencing cultural identity today.